How Can South Asia Turn Its Proximity from a Burden to an Advantage? - Kathuria, Sanjay; Mathur, Priya (World Bank, Washington, DC, 2019)
Around the world, trade has played a critical role in reducing poverty. Some of the most successful countries in East Asia, Europe, and North America owe much of their success to strong trade relations with their neighbors. However, South Asian countries have yet to reap the benefits of proximity. Intraregional trade accounts for a little more than 5 percent of South Asia’s total trade, compared with 50 percent in East Asia and the Pacific and 22 percent in Sub-Saharan Africa.The World Bank’s recent report, A Glass Half Full: The Promise of Regional Trade in South Asia, clearly illustrates the gaps between current and potential trade in South Asia.The force of gravity—the degree of trade attraction between countries—is also manifest in high levels of informal trade. Informal trade has been estimated at 50 percent of formal trade in South Asia, aggregating assessments of various studies covering the 1993 to 2005 period.The large gaps between actual and potential trade arise because South Asian trade regimes discriminate against each other. This can be shown through an index of trade restrictiveness. Based on global trade data, such an index generates an implicit tariff that measures a country’s tariff and non-tariff barriers on imports. In India, Pakistan, and Sri Lanka, the index is two to nine times higher for imports from South Asia than from the rest of the world.Moreover, although the average burden of non-tariff measures may not appear high, it is high for specific product and market combinations in South Asia. It varies from over 75 percent to over 2,000 percent. Sri Lanka consistently appears on the list of product-market combinations with the highest trade restrictiveness index in the region. Barriers that have held back trade and investment within South Asia include tariffs and para tariffs, real and perceived non-tariff barriers, connectivity costs as manifested in the cost of air travel, and the broader trust deficit.